2019
DOI: 10.1016/j.jacc.2018.10.079
|View full text |Cite
|
Sign up to set email alerts
|

Direct Current Cardioversion of Atrial Arrhythmias in Adults With Cardiac Amyloidosis

Abstract: BACKGROUND Arrhythmias, conduction abnormalities, and intracardiac thrombus are common in patients with cardiac amyloidosis (CA). Outcomes of direct-current cardioversion (DCCV) for atrial arrhythmias in patients with CA are unknown. OBJECTIVES This study sought to examine DCCV procedural outcomes in patients with CA. METHODS Patients with CA scheduled for DCCV for atrial arrhythmias from January 2000 through December 2012 were identified and matched 2:1 with control patients by age, sex, type of atrial ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
2
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(93 citation statements)
references
References 36 publications
4
75
2
12
Order By: Relevance
“…10 Anticoagulation has been suggested for prophylaxis, but one study found a high rate of atrial clots prior to cardioversion despite adequate anticoagulation. 12 One autopsy series found atrial thrombi in 33% of patients with cardiac amyloidosis and thromboembolism in 20% of these patients. 13 The thromboembolism was fatal in 83% of cases.…”
mentioning
confidence: 99%
“…10 Anticoagulation has been suggested for prophylaxis, but one study found a high rate of atrial clots prior to cardioversion despite adequate anticoagulation. 12 One autopsy series found atrial thrombi in 33% of patients with cardiac amyloidosis and thromboembolism in 20% of these patients. 13 The thromboembolism was fatal in 83% of cases.…”
mentioning
confidence: 99%
“…However, it has been reported that while direct current cardioversion for atrial arrhythmias in patients with cardiac amyloidosis improved cardiac function, the complication rate of bradycardic and tachyarrhythmias events were high 21 . In addition, regarding pacemaker implantation, there are many unsolved problems such as the timing of implantation, pacing site and mode 22 .…”
Section: Atrioventricular Block Is Detected As a Complication In 15-2mentioning
confidence: 99%
“…Rhythm Control in CA. A recent study described direct current cardioversion procedural outcomes in patients with CA [47]. Although the success rate of restoration of the sinus rhythm was high, tachyarrhythmias and bradyarrhythmias complicating direct current cardioversion were significantly more frequent in CA patients compared with control patients (14 vs. 0%).…”
Section: Electrophysiological Abnormalities In Camentioning
confidence: 99%
“…Importantly, intracardiac thrombus was detected in 28% of CA patients referred for transesophageal guided direct cardioversion, including patients who did not require transesophageal guidance per guidelines (either had a therapeutic level of anticoagulation for >3 weeks or arrhythmia onset <48 h before the planned cardioversion) [47]. Thus, transesophageal echocardiography should strongly be considered before direct cardioversion in all patients with CA, regardless of the duration of arrhythmia or the therapeutic level of anticoagulation [47, 53].…”
Section: Electrophysiological Abnormalities In Camentioning
confidence: 99%